Exploiting Multifunctionality of M2+ (M=Co2+, Ni2+) Phosphides for Electrocatalysis toward HER, OER and ORR - Pérez-Colodrero, Rosario Mercedes; Bazaga-García, Montse; Vílchez-Cózar, Álvaro; Olivera-Pastor, Pascual; Cabeza-Díaz, Aurelio (My University, 2022)
INTRODUCTION The scarcity and high cost of Pt and Ru/Ir-based noble metal electrocatalysts forces to design alternative low-cost and efficient materials for sustainable energy storage and conversion technologies1. Among them, phosphorus-containing coordination polymers, such as metal phosphonates and phosphinates, have emerged as potential precursors of transition-metal phosphide (TMP) electrocatalysts2. EXPERIMENTAL STUDY Pyrolysis under 5%H2-Ar atmosphere at different temperatures. Electrocatalytic performances were investigated toward Oxygen Evolution Reaction (OER), Oxygen Reduction Reaction (ORR) and Hydrogen Evolution Reaction (HER). RESULTS AND DISCUSSION In this research-work, we report the synthesis and crystal structure of several families of divalent metal (Co2+, Ni2+) derived from the (2-carboxyethyl)(phenyl)phosphinic acid (CEPPA)3 and etidronic acid4. These solids were used as precursor of metal phosphides (M2P/MP) by thermal reduction under 5%H2-Ar atmosphere at different temperatures and their electrocatalytic performances were investigated toward OER, ORR and HER. The relationship between M/P molar ratios and/or the M2+ coordination environment in the precursor structures and the electrocatalytic activity of the prepared metal phosphides will be discussed. The presence/absence of N-doped carbon graphitic matrix in the final materials will be also studied
Keywords: Oxygen Evolution Reaction (OER); Oxygen Reduction Reaction (ORR); Hydrogen Evolution Reaction (HER); Electrocatalysts; Transition-metal phosphide